2012
DOI: 10.1128/mcb.06529-11
|View full text |Cite
|
Sign up to set email alerts
|

An Evi1-C/EBPβ Complex Controls Peroxisome Proliferator-Activated Receptor γ2 Gene Expression To Initiate White Fat Cell Differentiation

Abstract: Fibroblastic preadipocyte cells are recruited to differentiate into new adipocytes during the formation and hyperplastic growth of white adipose tissue. Peroxisome proliferator-activated receptor ␥ (PPAR␥), the master regulator of adipogenesis, is expressed at low levels in preadipocytes, and its levels increase dramatically and rapidly during the differentiation process. However, the mechanisms controlling the dynamic and selective expression of PPAR␥ in the adipocyte lineage remain largely unknown. We show h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 49 publications
2
21
0
Order By: Relevance
“…Following growth arrest, efficient induction of 3T3-L1 cell differentiation is accompanied by mitotic clonal expansion (MCE) [28]. Studies have shown that EVI1 stimulates cell proliferation [29] and this property may stimulate MCE, contributing to the enhanced expression of adipogenic markers observed here, which are consistent with previous observations [11].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Following growth arrest, efficient induction of 3T3-L1 cell differentiation is accompanied by mitotic clonal expansion (MCE) [28]. Studies have shown that EVI1 stimulates cell proliferation [29] and this property may stimulate MCE, contributing to the enhanced expression of adipogenic markers observed here, which are consistent with previous observations [11].…”
Section: Discussionsupporting
confidence: 91%
“…The relative abundance of splice variants has not been determined in this study but others have shown that general EVI1 expression is low in proliferating preadipocytes, transiently peaks during chemical stimulation of differentiation then is low again for the remaining programme [11].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Primary inguinal cells were grown and differentiated as above with the inclusion of 1 µM rosiglitazone through differentiation. Oil-Red-O, virus production, and transfection assays were performed as described previously (Ishibashi et al 2012). The following constructs were used in cell culture: pMX-BRG1 (Hans Schöler; Addgene, plasmid no.…”
Section: Cell Culturementioning
confidence: 99%
“…The increased level of the development of fat and creates adipose tissue obesity which mediates insulin resistance 14 . The PPAR-γ plays the major regulator for adipogenesis, which expressed specifically in adipose tissue [15][16][17] . It was found that adiponectin is directly affected by obesity and the correlation between adiponectin and Body Mass Index 18 .…”
mentioning
confidence: 99%